CALCULATION IN COMMON WORK REINFORCED CONCRETE PLATE FLOOR WITH REINFORCEMENT CONCRETE FOR FLOOR INDUSTRIAL BUILDING (Municipal economy of cities. Series: «Economy science», 2015)
This article discusses two options for calculating ribbed concrete industrial slabs: without teamwork reinforced footings with stove and taking into account teamwork. Teamwork footings with stove leads to a significant increase in total hardness plate, if the value of the upper layer of reinforced concrete up to 150-200 mm or more in parallel reduces the required reinforcement plates by increasing the useful load on the overlap by 50-70%. This takes into account the actual existing damage plates (in particular, a protective layer of concrete chips, impregnation whole body plate podtekayuschimi oils of machine equipment, lowering the elastic modulus of concrete is 25-30%, еffect of elevated temperatures on the physico-mechanical properties of the concrete). Constructive calculation of a reinforced concrete slab for the two options of loading it (excluding joint work plate with the top layer of concrete and based on this work) was carried out on software complex «SCAD», version 11.5. The second option reduces the deformability plates 3-4 times, reduces the reinforcement of 2-3. Keywords: strength, deformability, concrete slabs, footings, joint work.